Islamic Financial Inclusion and the Empowerment of Micro Enterprises in Remote Regions - Meili Mahera, Rofiqo; Ilham, M; Albahi, Muhammad (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study explores the role of Islamic Financial Institutions (IFIs) in enhancing access to microenterprise financing in rural Indonesia through a qualitative literature review approach. Drawing on 25 peer-reviewed sources published between 2019 and 2024, the research identifies four key dimensions: institutional outreach, rural access barriers, effectiveness of sharia contracts, and integration of social and digital finance. Findings reveal that although IFIs have grown significantly in terms of assets and regulatory structure, their inclusion strategies remain inadequate for rural populations. Sharia-based contracts like mudharabah and musyarakah are underutilized due to operational complexities and lack of financial literacy. Moreover, the integration of zakat and other social finance tools with digital platforms is still fragmented. The study emphasizes that Islamic finance must move beyond formal compliance toward ethical inclusivity by addressing structural, behavioral, and technological barriers. The research concludes that achieving maqashid shariah in microfinance requires institutional reform, cross-sector collaboration, and a renewed commitment to justice, transparency, and community empowerment.